Back Cover: Visible‐Light, Photoredox‐Mediated Oxidative Tandem Nitroso‐Diels–Alder Reaction of Arylhydroxylamines with Conjugated Dienes (Eur. J. Org. Chem. 15/2017). Issue 15 (12th April 2017) - Santacroce, Veronica; Duboc, Raphael; Malacria, Max; Maestri, Giovanni; Masson, Geraldine
Abstract : The cover picture shows the nitroso‐Diels–Alder reaction between hydroxylamines and conjugated dienes. This tandem process is achieved by an in situ aerobic oxidation. In fact, the Ru 2+ photocatalyst can selectively oxidize hydroxylamines to nitroso intermediates, allowing the one‐pot synthesis of the desired 3, 6‐dihydro‐1, 2‐oxazines. These oxidizing conditions show a broad functional‐group tolerance towards both reaction partners, validating the synthetic potential of the method. Details are discussed in the Communication by G. Masson et al. on page 2095 ff (DOI:10.1002/ejoc.201601492 ).